Usage of compact compression specimens to determine non-linear fracture parameters of concrete - Ince, Ragip (Wiley, 2021)
Up to now, the compact compression specimens (CCS) have only been used to estimate the fracture toughness parameter of cement-based materials. In the study, the linear elastic fracture mechanics formulae of CCS, namely, the universal weight functions with four terms, K-I (stress intensity factor), CMOD (crack mouth opening displacement), and COD (crack opening displacement) profile were, therefore, derived using the finite element method. To investigate the extent to which CCS tests could model the non-linear fracture behaviour of concrete, 11 series of tests in the literature were subsequently examined for the effective crack models: the two-parameter model, the size effect model, and the double-K model. Two prediction formulae based on previous test data were proposed to estimate unstable fracture toughness and initiation fracture toughness of concrete. The results of CCS test-based non-linear fracture mechanics look viable and very promising.
Keywords: boundary element method; compact compression test; double? K model; finite element method; size effect model; two? parameter model